Polymer Composition for Use in Antenna Systems - Patent application

By using thermal etropic liquid crystal polymer and dielectric material in polymer compositions to adjust the volume resistivity, the problem that existing materials are difficult to achieve high dielectric constant and low dielectric loss at high frequencies and high temperatures is solved, and high-performance materials suitable for multi-anti-conductor systems are realized.

JP7653412B2Active Publication Date: 2025-03-28TICONA LLC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2022506888
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-06-15
Filing Date
2020-08-19
Publication Date
2025-03-28
Estimated Expiration
2040-08-19

AI Technical Summary

Technical Problem

When forming anti-conductor systems, it is difficult for existing materials to achieve high dielectric constant and low dielectric loss resonance at the same time, and it is not applicable to applications with high temperature and mechanical properties.

Method used

By using a polymer composition containing a thermal etropic liquid crystal polymer, the dielectric constant reaches 4 or above and the dielectric loss resonance reaches 0.3 or below by adjusting the volume resistivity of the dielectric material.

Benefits of technology

A polymer composition with high dielectric constant and low dielectric loss at high frequencies is achieved, with good thermal and mechanical properties, suitable for high temperature and high frequency applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007653412000029
    Figure 0007653412000029
  • Figure 0007653412000030
    Figure 0007653412000030
  • Figure 0007653412000031
    Figure 0007653412000031
Patent Text Reader

Abstract

A polymer composition is provided that includes a dielectric material distributed within a polymer matrix. The dielectric material has a resistivity of about 0.1 ohm·cm to about 1×10 12 The polymer composition has a volume resistivity of ohm·cm, the polymer matrix contains at least one thermotropic liquid crystalline polymer, and further, the polymer composition exhibits a relative dielectric constant of greater than or equal to about 4 and a dielectric loss tangent of less than or equal to about 0.3, as determined at a frequency of 2 GHz.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] Cross-reference of related questions

[0001] This application is a part of U.S. Provisional Patent Application No. 62 / 889,792, having a filing date of August 21, 2019; U.S. Provisional Patent Application No. 62 / 898,188, having a filing date of September 10, 2019; U.S. Provisional Patent Application No. 62 / 925,271, having a filing date of October 24, 2019; U.S. Provisional Patent Application No. 62 / 925,271, having a filing date of December 20, 2019, which are incorporated by reference in their entireties herein. This application claims the benefit of U.S. Provisional Patent Application No. 62 / 951,033; U.S. Provisional Patent Application No. 62 / 958,003, which has a filing date of January 7, 2020; U.S. Provisional Patent Application No. 62 / 972,201, which has a filing date of February 10, 2020; U.S. Provisional Patent Application No. 63 / 024,579, which has a filing date of May 14, 2020; and U.S. Provisional Patent Application No. 63 / 038,980, which has a filing date of June 15, 2020. [Background technology]

[0002]

[0002] Molded interconnect devices ("MIDs") often contain a plastic substrate on which conductive elements or paths are formed to form antenna systems for various electronic components. Such MID devices are therefore three-dimensional molded parts with integrated printed conductors or circuit layouts. Formation of MIDs using a laser direct structuring ("LDS") process is becoming increasingly popular, in which a computer-controlled laser beam moves over the plastic substrate and activates its surface where the conductive paths should be located. Using the laser direct structuring process, conductive element widths and spacings of 150 microns or less can be obtained. As a result, MIDs formed from this process reduce space and weight in the final application. Another advantage of laser direct structuring is its flexibility. Various materials have been proposed to form the plastic substrate of laser direct structured MID devices. For example, one such material is a blend of polycarbonate, acrylonitrile butadiene styrene ("ABS"), copper chromium oxide spinel, and bisphenol A diphenyl phosphate ("BPADP") flame retardant. However, one problem with such materials is that the flame retardants tend to adversely affect the mechanical properties (e.g., load deflection temperature) of the composition, making them difficult to use in laser direct structuring processes. Such materials are also not suitable for lead-free soldering processes (surface mount technology) that require high temperature resistance. Another problem is that the materials tend to have low dielectric constants and high dissipation factors, making them difficult to use in applications where it is desired to include more than one antenna in the device. Summary of the Invention [Problem to be solved by the invention]

[0003]

[0003] Thus, a need exists for polymer compositions having a relatively high dielectric constant and low dielectric loss tangent for use in antenna systems. [Means for solving the problem]

[0004] According to one embodiment of the present invention, a polymer composition is disclosed that includes a dielectric material distributed in a polymer matrix. The dielectric material has a dielectric constant between about 0.1 ohm·cm and about 1×10 12 The polymer matrix contains at least one thermotropic liquid crystalline polymer, and the polymer composition exhibits a dielectric constant of greater than or equal to about 4 and a dielectric loss tangent of less than or equal to about 0.3, determined at a frequency of 2 GHz.

[0005]

[0005] Other features and aspects of the present invention are described in more detail below.

[0006] A full and enabling disclosure of the present invention, including the best mode thereof, to one of ordinary skill in the art, is set forth more particularly in the remainder of the specification, including reference to the accompanying drawings, in which: [Brief description of the drawings]

[0006] [Figure 1]

[0007] FIG. 1 is a front perspective view of an embodiment of an electronic component that can utilize the antenna system. [Diagram 2] FIG. 1 is a rear perspective view of an embodiment of an electronic component that can utilize the antenna system. [Diagram 3]

[0008] FIG. 2 is a top view of an exemplary inverted-F antenna resonating element for one embodiment of the antenna system. [Figure 4]

[0009] FIG. 2 is a top view of an exemplary monopole antenna resonating element for one embodiment of the antenna system. [Diagram 5]

[0010] FIG. 2 is a top view of an exemplary slot antenna resonating element for one embodiment of the antenna system. [Figure 6]

[0011] FIG. 2 is a top view of an exemplary patch antenna resonating element for one embodiment of the antenna system. [Figure 7]

[0012] FIG. 2 is a top view of an exemplary multi-branch inverted-F antenna resonating element for one embodiment of the antenna system. [Figure 8]

[0013] FIG. 1 is a diagram of a 5G antenna system including a base station, one or more relay stations, one or more user computing devices, and one or more Wi-Fi repeaters according to an embodiment of the present disclosure. [Figure 9A]

[0014] FIG. 1 illustrates a top view of an exemplary user computing device including a 5G antenna in accordance with an aspect of the present disclosure. [Figure 9B]

[0015] FIG. 9B is a side view of the example user computing device of FIG. 9A including a 5G antenna according to an embodiment of the present disclosure. [Figure 10]

[0016] FIG. 9B is an expanded view of a portion of the user computing device of FIG. 9A. [Figure 11]

[0017] FIG. 1 is a side view of a coplanar waveguide antenna array configuration according to an aspect of the present disclosure. [Figure 12A]

[0018] FIG. 1 is a diagram of an antenna array for a large scale multiple-input multiple-output configuration in accordance with an aspect of the present disclosure. [Figure 12B]

[0019] FIG. 1 is a diagram of an antenna array formed by laser direct structuring according to an aspect of the present disclosure. [Figure 12C]

[0020] FIG. 1 is a diagram of an exemplary antenna configuration according to an aspect of the present disclosure. [Figure 13A]

[0021] FIG. 13A is a simplified sequence diagram of a laser direct structuring manufacturing method that can be used to form the antenna system. [Figure 13B] FIG. 13B is a simplified sequence diagram of a laser direct structuring manufacturing method that can be used to form the antenna system. [Figure 13C] FIG. 13C is a simplified sequence diagram of a laser direct structuring manufacturing method that can be used to form the antenna system. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007]

[0022] It will be understood by those skilled in the art that this discussion is merely a description of exemplary embodiments and is not intended to limit the broader aspects of the invention.

[0023] In general, the present invention relates to a polymeric composition containing a dielectric material distributed within a polymeric matrix that includes a thermotropic liquid crystal polymer. The inventors have discovered that by selectively controlling various aspects of the composition (e.g., the volume resistivity of the dielectric material), the resulting composition can maintain a unique combination of high dielectric constant and low dissipation factor for use in antenna systems. For example, the polymeric composition may exhibit a high dielectric constant of about 4 or more, in some embodiments about 8 or more, in some embodiments about 10 or more, in some embodiments about 10 to about 30, in some embodiments about 11 to about 25, and in some embodiments about 12 to about 24, as determined by split post resonance at a frequency of 2 GHz. Such a high dielectric constant can facilitate the ability to form thin substrates and further enable the utilization of multiple conductive elements (e.g., antennas) operating simultaneously with only minimal levels of electrical interference. The dielectric loss tangent, which is a measure of the rate of energy loss, may also be relatively low, e.g., about 0.3 or less, in some embodiments about 0.1 or less, in some embodiments about 0.06 or less, in some embodiments about 0.04 or less, in some embodiments about 0.01 or less, and in some embodiments about 0.001 to about 0.006, as determined by split post resonance at a frequency of 2 GHz. In particular, the inventors have also surprisingly discovered that the dielectric constant and dielectric loss tangent can be maintained within the above-mentioned ranges even when exposed to various temperatures, such as temperatures from about -30°C to about 100°C. For example, when subjected to the thermal cycling test described herein, the ratio of the dielectric constant after thermal cycling to the initial dielectric constant may be about 0.8 or more, in some embodiments about 0.9 or more, and in some embodiments about 0.91 to about 1. Similarly, the ratio of the dissipation factor after exposure to high temperatures to the initial dissipation factor may be about 1.3 or less, in some embodiments about 1.2 or less, in some embodiments about 1.1 or less, in some embodiments about 1.0 or less, in some embodiments about 0.95 or less, in some embodiments about 0.1 to about 0.9, and in some embodiments about 0.2 to about 0.8. The change in dissipation factor (i.e., initial dissipation factor minus dissipation factor after thermal cycling) may also range from about -0.1 to about 0.1, in some embodiments about -0.05 to about 0.01, and in some embodiments about -0.001 to 0.

[0008]

[0024] Traditionally, it was believed that polymer compositions having a combination of high dielectric constant and low dielectric loss tangent do not simultaneously have sufficiently good thermal, mechanical properties and ease of processing (i.e., low viscosity) to enable their use in certain types of applications. However, in contrast to conventional thinking, it has been found that polymer compositions have both excellent thermal, mechanical properties and processability. The melting temperature of the composition may be, for example, from about 250°C to about 440°C, in some embodiments from about 270°C to about 400°C, and in some embodiments from about 300°C to about 380°C. Even at such melting temperatures, the ratio of the temperature deflection under load ("DTUL") to the melting temperature, which is a measure of short-term heat resistance, may still remain relatively high. For example, the ratio may range from about 0.5 to about 1.00, in some embodiments from about 0.6 to about 0.95, and in some embodiments from about 0.65 to about 0.85. Particular DTUL values ​​may range, for example, from about 200° C. to about 350° C., in some embodiments from about 210° C. to about 320° C., and in some embodiments, from about 230° C. to about 290° C. Such high DTUL values ​​may, among other things, enable the use of fast and reliable surface mounting processes for mating the structure and other components of the electrical component.

[0009]

[0025] Additionally, the polymer composition may have high impact strength, useful in forming thin substrates. The composition may have a hardness of, for example, about 0.5 kJ / m2, as determined according to ISO Test No. ISO 179-1:2010 at a temperature of 23° C. 2 In some embodiments, about 1 to about 60 kJ / m 2 In some embodiments, from about 5 to about 50 kJ / m 2 In some embodiments, from about 20 to about 45 kJ / m 2The composition may also have a notched Charpy impact strength of about 20 to about 500 MPa, in some embodiments about 50 to about 400 MPa, and in some embodiments about 70 to about 350 MPa; a tensile break strain of about 0.4% or more, in some embodiments about 0.5% to about 10%, and in some embodiments about 0.6% to about 3.5%; and / or a tensile modulus of about 5,000 MPa to about 20,000 MPa, in some embodiments about 8,000 MPa to about 20,000 MPa, and in some embodiments about 10,000 MPa to about 20,000 MPa. Tensile properties may be determined according to ISO Test No. 527:2012 at a temperature of 23°C. Additionally, the polymer composition may exhibit a flexural strength of about 20 to about 500 MPa, in some embodiments about 50 to about 400 MPa, and in some embodiments about 100 to about 350 MPa; a flexural elongation of about 0.4% or greater, in some embodiments about 0.5% to about 10%, and in some embodiments about 0.6% to about 3.5%; and / or a flexural modulus of about 5,000 MPa to about 20,000 MPa, in some embodiments about 8,000 MPa to about 20,000 MPa, and in some embodiments about 10,000 MPa to about 15,000 MPa. Flexural properties may be determined according to 178:2010 at a temperature of 23°C.

[0010]

[0026] Various embodiments of the invention will now be described in more detail. I. Polymer Composition A. Polymer matrix

[0027] The polymer matrix contains one or more liquid crystal polymers, generally in an amount of about 15 wt.% to about 85 wt.%, in some embodiments about 20 wt.% to about 75 wt.%, and in some embodiments about 30 wt.% to about 50 wt.% of the total polymer composition. Liquid crystal polymers are generally classified as "thermotropic" as long as they have a rod-like structure and can exhibit crystalline behavior in their molten state (e.g., a thermotropic nematic state). Liquid crystal polymers utilized in the polymer composition typically have a melting temperature of about 200°C or higher, in some embodiments about 220°C to about 350°C, and in some embodiments about 240°C to about 300°C. The melting temperature may be determined as known in the art using differential scanning calorimetry ("DSC"), for example, by ISO Test No. 11357-3:2011. Such polymers may be formed from one or more types of repeating units, as known in the art. The liquid crystal polymer may be, for example, a polymer represented by the following formula (I):

[0011] [ka]

[0012] (In the formula, Ring B is a substituted or unsubstituted 6-membered aryl group (e.g., 1,4-phenylene or 1,3-phenylene), a substituted or unsubstituted 6-membered aryl group fused to a substituted or unsubstituted 5- or 6-membered aryl group (e.g., 2,6-naphthalene), or a substituted or unsubstituted 6-membered aryl group linked to a substituted or unsubstituted 5- or 6-membered aryl group (e.g., 4,4-biphenylene); Y1 and Y2 are independently O, C(O), NH, C(O)HN, or NHC(O). The aromatic ester may contain one or more aromatic ester repeat units generally represented by:

[0013]

[0028] Typically, at least one of Y1 and Y2 is C(O). Examples of such aromatic ester repeat units include, for example, aromatic dicarboxylic acid repeat units (in formula I, Y1 and Y2 are C(O)), aromatic hydroxycarboxylic acid repeat units (in formula I, Y1 is O and Y2 is C(O)), and various combinations thereof.

[0014]

[0029] For example, aromatic hydroxycarboxylic acid repeat units derived from aromatic hydroxycarboxylic acids such as 4-hydroxybenzoic acid; 4-hydroxy-4'-biphenylcarboxylic acid; 2-hydroxy-6-naphthoic acid; 2-hydroxy-5-naphthoic acid; 3-hydroxy-2-naphthoic acid; 2-hydroxy-3-naphthoic acid; 4'-hydroxyphenyl-4-benzoic acid; 3'-hydroxyphenyl-4-benzoic acid; 4'-hydroxyphenyl-3-benzoic acid, and the like, as well as alkyl, alkoxy, aryl, and halogen substituted versions thereof, and combinations thereof, may be utilized. Particularly suitable aromatic hydroxycarboxylic acids are 4-hydroxybenzoic acid ("HBA") and 6-hydroxy-2-naphthoic acid (HNA). When utilized, repeat units derived from hydroxycarboxylic acids (e.g., HBA and / or HNA) typically comprise about 20 mol.% or more of the polymer, in some embodiments from about 30 mol.% to about 70 mol.%, and in some embodiments from about 35 mol.% to 60 mol.%.

[0015]

[0030] Aromatic dicarboxylic acid repeat units derived from aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, 2,6-naphthalenedicarboxylic acid, diphenylether-4,4'-dicarboxylic acid, 1,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, 4,4'-dicarboxybiphenyl, bis(4-carboxyphenyl)ether, bis(4-carboxyphenyl)butane, bis(4-carboxyphenyl)ethane, bis(3-carboxyphenyl)ether, bis(3-carboxyphenyl)ethane, and the like, as well as alkyl, alkoxy, aryl, and halogen substituted versions thereof, and combinations thereof, may also be utilized. Particularly suitable aromatic dicarboxylic acids can include, for example, terephthalic acid ("TA"), isophthalic acid ("IA"), and 2,6-naphthalenedicarboxylic acid ("NDA"). When utilized, repeat units derived from aromatic dicarboxylic acids (e.g., IA, TA, and / or NDA) typically comprise from about 1 mol.% to about 50 mol.%, in some embodiments from about 10 mol.% to about 45 mol.%, and in some embodiments, from about 20 mol.% to about 40 mol.% of the polymer.

[0016]

[0031] Other repeat units may also be utilized in the polymer. For example, in certain embodiments, repeat units derived from aromatic diols such as hydroquinone, resorcinol, 2,6-dihydroxynaphthalene, 2,7-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 4,4'-dihydroxybiphenyl (or 4,4'-biphenol), 3,3'-dihydroxybiphenyl, 3,4'-dihydroxybiphenyl, 4,4'-dihydroxybiphenyl ether, bis(4-hydroxyphenyl)ethane, and the like, as well as alkyl, alkoxy, aryl, and halogen substituted versions thereof, and combinations thereof, may be utilized. Particularly suitable aromatic diols include, for example, hydroquinone ("HQ") and 4,4'-biphenol ("BP"). When utilized, repeat units derived from aromatic diols (e.g., HQ and / or BP) typically comprise from about 1 mol.% to about 50 mol.%, in some embodiments from about 10 to about 45 mol.%, and in some embodiments from about 20 mol.% to about 40 mol.% of the polymer. Repeat units such as those derived from aromatic amides (e.g., acetaminophen ("APAP")), and / or aromatic amines (e.g., 4-aminophenol ("AP"), 3-aminophenol, 1,4-phenylenediamine, 1,3-phenylenediamine, etc.) may also be utilized. When utilized, repeat units derived from aromatic amides (e.g., APAP) and / or aromatic amines (e.g., AP) typically comprise from about 0.1 mol.% to about 20 mol.%, in some embodiments from about 0.5 mol.% to about 15 mol.%, and in some embodiments from about 1 mol.% to about 10 mol.% of the polymer. It should also be understood that various other monomeric repeat units may be incorporated into the polymer. For example, in certain embodiments, the polymer may contain one or more repeat units derived from non-aromatic monomers, such as aliphatic or alicyclic hydroxycarboxylic acids, dicarboxylic acids, diols, amides, amines, and the like. Of course, in other embodiments, the polymer may be "fully aromatic" in that it does not include repeat units derived from non-aromatic (e.g., aliphatic or alicyclic) monomers.

[0017]

[0032] Although not required, the liquid crystal polymer may be a "high naphthene" polymer so long as it contains a relatively high content of repeat units derived from naphthenic hydroxycarboxylic acids and naphthenic dicarboxylic acids, such as naphthalene-2,6-dicarboxylic acid ("NDA"), 6-hydroxy-2-naphthoic acid ("HNA"), or combinations thereof. That is, the total amount of repeat units derived from naphthenic hydroxycarboxylic acids and / or dicarboxylic acids (e.g., NDA, HNA, or combinations of HNA and NDA) is typically about 10 mol.% or more, in some embodiments about 15 mol.% or more, and in some embodiments about 20 mol.% to about 60 mol.% of the polymer. Unlike many conventional "low naphthene" polymers, it is believed that the resulting "high naphthene" polymers can exhibit good thermal and mechanical properties. In one particular embodiment, for example, repeat units derived from naphthalene-2,6-dicarboxylic acid ("NDA") may comprise from about 10 mol.% to about 40 mol.%, in some embodiments from about 12 mol.% to about 35 mol.%, and in some embodiments, from about 15 mol.% to about 30 mol.% of the polymer.

[0018] B. Dielectric Materials

[0033] To aid in achieving desired dielectric properties, the polymer composition also contains a dielectric material. The dielectric material is typically utilized in an amount of about 10 wt.% to about 70 wt.%, in some embodiments about 20 wt.% to about 60 wt.%, and in some embodiments about 30 wt.% to about 50 wt.% of the composition. As noted above, the volume resistivity of the dielectric material is selectively controlled to be generally semiconductive in nature. For example, the dielectric material may have a volume resistivity of about 0.1 ohm·cm to about 1×10, determined, for example, according to ASTM D257-14 at a temperature of about 20° C. 12 ohm cm, in some embodiments from about 0.5 ohm cm to about 1 x 10 11 ohm cm, in some embodiments, from about 1 to about 1 x 10 10 ohm cm, in some embodiments, from about 2 to about 1 x 10 8It may have a volume resistivity in ohms·cm. This may be achieved by selecting a single material with the desired volume resistivity, or by blending multiple materials together (e.g., insulating and conductive) such that the resulting blend has the desired volume resistivity.

[0019]

[0034] In one embodiment, for example, inorganic oxide materials may be utilized that may exhibit a linear response of charge (or polarization) versus voltage. These materials may exhibit a total reversible polarization of charge within the crystal structure after an applied electric field is removed. Suitable inorganic oxide materials for this purpose may include, for example, ferroelectric and / or paraelectric materials. Examples of suitable ferroelectric materials include, for example, barium titanate (BaTiO3), strontium titanate (SrTiO3), calcium titanate (CaTiO3), magnesium titanate (MgTiO3), barium strontium titanate (SrBaTiO3), sodium barium niobate (NaBa2Nb5O4), and the like. 15 ), potassium barium niobate (KBa2Nb5O 15 ), calcium zirconate (CaZrO3), titanite (CaTiSiO5), and combinations thereof. Further examples of suitable paraelectric materials include, for example, titanium dioxide (TiO2), tantalum pentoxide (Ta2O5), hafnium dioxide (HfO2), niobium pentoxide (Nb2O5), alumina (Al2O3), zinc oxide (ZnO), and the like, and combinations thereof. Particularly suitable inorganic oxide materials are particles containing TiO2, BaTiO3, SrTiO3, CaTiO3, MgTiO3, BaSrTi2O6, and ZnO. Of course, other types of inorganic oxide materials (e.g., mica) can also be used as the dielectric material. Carbon materials such as graphite, carbon black, and the like can be used as well.

[0020]

[0035] The shape and size of the dielectric material are not particularly limited and may include particles, fine powders, fibers, whiskers, tetrapods, plates, and the like. For example, in one embodiment, the dielectric material may include particles having an average diameter of about 0.01 to about 100 micrometers, and in some embodiments, about 0.10 to about 20 micrometers. In another embodiment, the dielectric material may include fibers and / or whiskers having an average diameter of about 0.1 to about 35 micrometers, and in some embodiments, about 0.2 to about 20 micrometers, and in some embodiments, about 0.5 to about 15 micrometers. When utilized, the whiskers may have an aspect ratio of about 1 to about 100, and in some embodiments, about 2 to about 80, and in some embodiments, about 4 to about 50. The volume average length of such whiskers may range, for example, from about 1 to about 200 micrometers, and in some embodiments, from about 2 to about 150 micrometers, and in some embodiments, from about 5 to about 100 micrometers.

[0021]

[0036] Various techniques may be utilized to facilitate achieving the desired volume resistivity. For example, in one embodiment, inorganic oxide materials may be utilized having a volume resistivity of 0.1 ohm·cm to about 500 ohm·cm, in some embodiments, about 0.5 ohm·cm to about 250 ohm·cm, in some embodiments, about 1 to about 100 ohm·cm, and in some embodiments, about 2 to about 50 ohm·cm, as determined, for example, at a temperature of about 20° C. according to ASTM D257-14. One example of such a material is an inorganic oxide whisker having a three-dimensional structure (e.g., zinc oxide whisker). For example, the inorganic oxide whisker may have a central body and multiple needle-like crystals extending radially therefrom to form a three-dimensional structure. When such whiskers are incorporated into a resin, the needle-like crystals may be placed in close proximity to one another, thereby increasing the likelihood of forming a stable conductive path. The number of needle-like crystals may vary, for example, about 2 or more, in some embodiments, 3 to 8, and in some embodiments, 4 to 6 (e.g., 4). For example, if four needle-shaped crystals are present, the whiskers have a "tetrapod" morphology even though one or more of those needle-shaped crystal protrusions may break during processing and / or manufacturing. The central body and / or base portion of the needle-shaped crystals may have an average diameter within the ranges described above, for example, about 0.1 to about 35 micrometers, in some embodiments, about 0.2 to about 20 micrometers, and in some embodiments, about 0.5 to about 15 micrometers. The volume average length (base to tip) of the needle-shaped crystals may also have a volume average length within the ranges described above, for example, about 1 to about 200 micrometers, in some embodiments, about 2 to about 150 micrometers, and in some embodiments, about 5 to about 100 micrometers. Such whiskers may be formed by heat treating a metal powder (e.g., zinc) having an oxide film on its surface in an atmosphere containing molecular oxygen, as described, for example, in U.S. Patent No. 4,960,654 to Yoshinaka et al. One particularly suitable type of whisker having such characteristics includes single crystal tetrapod zinc oxide whiskers available from Panasonic under the trade name Pana-Tetra™.

[0022]

[0037] In another embodiment, the solubility of about 1×10 3 ~Approx. 1×10 12 ohm cm, in some embodiments, approximately 1×10 4 ~Approx. 1×10 11 ohm cm, in some embodiments, approximately 1×10 5 ~Approx. 1×10 10 ohm cm, in some embodiments, approximately 1×10 6 ~Approx. 1×10 8 Carbon materials having a volume resistivity of ohm·cm may be utilized. For example, carbon materials (e.g., particles, fibers, etc.) having a volume resistivity within the above range may be obtained by calcining an organic material (e.g., petroleum tar, petroleum pitch, coal tar or coal pitch) at high temperatures (e.g., 400° C. to 900° C.) in an inert atmosphere, as described, for example, in U.S. Patent No. 8,642,682 to Nishihata et al. The resulting carbon materials typically have a high carbon content, such as about 80 wt.% or more, in some embodiments about 85 wt.% or more, and in some embodiments about 90 wt.% to about 98 wt.%. One particularly suitable type of carbon material having such characteristics is available from Kureha Extron under the trade name Krefine™.

[0023]

[0038] Of course, as discussed above, conductive materials can be utilized in combination with insulating materials to help achieve a desired volume resistivity. Conductive materials generally have a resistivity of less than about 0.1 ohm-cm, and in some embodiments, less than about 1×10 -8 ~Approx. 1×10 -2 Insulating materials have a volume resistivity of about 1 x 10 Ohm cm. 12 Greater than ohm-cm, in some embodiments approximately 1×10 13 ~Approx. 1×10 18and having a volume resistivity of ohms·cm. Suitable conductive materials can include, for example, conductive carbon materials (e.g., graphite, carbon black, fibers, graphene, nanotubes, etc.), metals, and the like. Similarly, suitable insulating materials can include the inorganic oxide materials (e.g., particles) described above, such as titanium dioxide (TiO2). When utilized, the ratio of the weight percentage of the insulating material in the polymer composition to the weight percentage of the conductive material in the composition can be from about 3 to about 100, in some embodiments from about 3 to about 50, in some embodiments from about 3 to about 20, in some embodiments from about 7 to about 18, and in some embodiments from about 8 to about 15. For example, the conductive material may comprise about 1 wt.% to about 20 wt.%, in some embodiments about 3 wt.% to about 18 wt.%, and in some embodiments about 5 wt.% to about 15 wt.%, of the dielectric material, while the insulating material may comprise about 80 wt.% to about 99 wt.%, in some embodiments about 82 wt.% to about 97 wt.%, and in some embodiments about 85 wt.% to about 95 wt.% of the dielectric material. Similarly, the conductive material may comprise from about 0.1 wt.% to about 15 wt.%, in some embodiments from about 0.5 wt.% to about 12 wt.%, and in some embodiments, from about 1 wt.% to about 10 wt.%, of the polymer composition, while the insulating material may comprise from about 20 wt.% to about 60 wt.%, in some embodiments, from 25 wt.% to about 55 wt.%, and in some embodiments, from about 30 wt.% to about 50 wt.% of the polymer composition.

[0024] C. Optional Additives

[0039] A wide variety of additional additives may also be included in the polymer composition, such as lubricants, fibrous fillers, particulate fillers, thermally conductive fillers, pigments, antioxidants, stabilizers, surfactants, waxes, flame retardants, anti-sag additives, nucleating agents (e.g., boron nitride), flow modifiers, laser activatable additives, and other materials added to improve properties and processability.

[0025]

[0040] In some embodiments, the polymer composition may be "laser activatable" in the sense that it contains an additive that can be activated by a laser direct structuring ("LDS") process to form antenna elements. In such a process, the additive is exposed to a laser that causes the liberation of metal. The laser thereby patterns the conductive elements in the part, leaving a roughened surface containing embedded metal particles. These particles act as nuclei for crystal growth during a subsequent plating process (e.g., copper plating, gold plating, nickel plating, silver plating, zinc plating, tin plating, etc.). When utilized, the laser activatable additive typically comprises from about 0.1 wt.% to about 30 wt.%, in some embodiments from about 0.5 wt.% to about 20 wt.%, and in some embodiments from about 1 wt.% to about 10 wt.% of the polymer composition. The laser activatable additive generally comprises a spinel crystal, which may include two or more metal oxide cluster configurations within a definable crystal formation. For example, all crystal formations may be formed according to the following general formula: AB2O4 (In the formula, A is a metal cation having a valence of two, such as cadmium, chromium, manganese, nickel, zinc, copper, cobalt, iron, magnesium, tin, titanium, and the like, and combinations thereof; B is a metal cation having a valence of 3, such as chromium, iron, aluminum, nickel, manganese, tin, and combinations thereof. may have the following structure:

[0026]

[0041] Generally, A in the above formula provides the main cation component of the first metal oxide cluster, and B provides the main cation component of the second metal oxide cluster. These oxide clusters may have the same or different structures. For example, in one embodiment, the first metal oxide cluster has a tetrahedral structure and the second metal oxide cluster has an octahedral cluster. Nevertheless, the clusters can be combined to provide a single identifiable crystal type structure with increased sensitivity to electromagnetic radiation. Examples of suitable spinel crystals include, for example, MgAl2O4, ZnAl2O4, FeAl2O4, CuFe2O4, CuCr2O4, MnFe2O4, NiFe2O4, TiFe2O4, FeCr2O4, MgCr2O4, and the like. Copper chromium oxide (CuCr2O4) is particularly suitable for use in the present invention and is available from Shepherd Color Co. under the name "Shepherd Black 1GM".

[0027]

[0042] Fibrous fillers may also be utilized in the polymeric compositions to improve the thermal and mechanical properties of the compositions without significantly affecting electrical performance. Fibrous fillers typically include fillers that have a high degree of tensile strength relative to their mass. For example, the ultimate tensile strength of the fibers (determined according to ASTM D2101) is typically about 1,000 to about 15,000 megapascals ("MPa"), in some embodiments about 2,000 MPa to about 10,000 MPa, and in some embodiments about 3,000 MPa to about 6,000 MPa. To help maintain the desired dielectric properties, such high strength fibers may be formed from materials that are generally insulating in nature, such as glass, ceramic (e.g., alumina or silica), aramid (e.g., Kevlar® sold by EI duPont de Nemours, Wilmington, Delaware), polyolefins, polyesters, and the like. Glass fibers such as E-glass, A-glass, C-glass, D-glass, AR-glass, R-glass, S1-glass, S2-glass, etc. are particularly suitable.

[0028]

[0043] Although the fibers utilized in the fibrous filler may have a variety of different sizes, fibers having a particular aspect ratio may promote improved mechanical properties of the resulting polymer composition. That is, fibers having an aspect ratio (average length divided by nominal diameter) of about 5 to about 50, in some embodiments about 6 to about 40, and in some embodiments about 8 to about 25 are particularly useful. Such fibers may have a weight average length of, for example, about 100 to about 800 micrometers, in some embodiments about 120 to about 500 micrometers, in some embodiments about 150 to about 350 micrometers, and in some embodiments about 200 to about 300 micrometers. The fibers may also have a nominal diameter of about 6 to about 35 micrometers, and in some embodiments about 9 to about 18 micrometers. The relative amount of the fibrous filler may also be selectively controlled to promote achieving the desired mechanical and thermal properties without adversely affecting other properties of the composition, such as its flowability and dielectric properties. For example, the fibrous filler may comprise from about 1 wt.% to about 40 wt.%, in some embodiments from about 3 wt.% to about 30 wt.%, and in some embodiments, from about 5 wt.% to about 20 wt.% of the polymer composition. When utilized in combination with a laser activatable additive, the fibrous filler may also be utilized in a sufficient amount such that the weight ratio of the fibrous filler to the combined amount of dielectric material and laser activatable material is from about 0.05 to about 1, in some embodiments from about 0.05 to about 0.5, in some embodiments from about 0.06 to about 0.4, and in some embodiments from about 0.1 to about 0.3.

[0029] II. Formation

[0044] The components used to form the polymer composition may be combined together using any of a variety of different techniques known in the art. For example, in one particular embodiment, the liquid crystal polymer, the dielectric material, and other optional additives are melt processed as a mixture in an extruder to form the polymer composition. The mixture may be melt kneaded at a temperature of about 250°C to about 450°C in a single or multiple screw extruder. In one embodiment, the mixture may be melt processed in an extruder that includes multiple temperature zones. The temperature of each zone is typically set within about -60°C to about 25°C relative to the melt temperature of the liquid crystal polymer. By way of example, the mixture may be melt processed using a twin screw extruder, such as a Leistritz 18mm co-rotating fully intermeshing twin screw extruder. A general purpose screw design may be used to melt process the mixture. In one embodiment, the mixture containing all of the components may be fed into the feed port of the first barrel by a metered feeder. In another embodiment, different components may be added at different addition points of the extruder, as is known. For example, the liquid crystal polymer may be applied to a feed port, and certain additives (e.g., dielectric materials) may be fed at the same or different temperature zones located downstream therefrom. In either case, the resulting mixture can be melted, mixed, and then extruded through a die. The extruded polymer composition can then be quenched in a water bath to solidify, pelletized in a pelletizer, and then dried.

[0030]

[0045] The melt viscosity of the resulting composition is generally low enough to flow easily into a mold cavity to form a small sized circuit board. For example, in one particular embodiment, the polymer composition is melted at 1,000 s -1 The polymer may have a melt viscosity of from about 5 to about 100 Pa·s, in some embodiments from about 10 to about 95 Pa·s, and in some embodiments from about 15 to about 90 Pa·s, determined at a shear rate of from about 100 Pa·s. The melt viscosity may be determined in accordance with 11443:2005.

[0031] III. Substrate

[0046] After formation, the polymer composition may be molded into the shape of a substrate desired for use in an antenna system. Due to the beneficial properties of the polymer composition, the resulting substrate may have a very small size, such as a thickness of about 5 millimeters or less, in some embodiments about 4 millimeters or less, and in some embodiments about 0.5 to about 3 millimeters. Typically, molded parts are molded using a one-component injection molding process in which dried and preheated plastic granules are injected into a mold. The conductive elements may be formed by various methods, such as plating, electroplating, and laser direct structuring. For example, when containing spinel crystals as a laser activatable additive, activation with a laser may result in a physicochemical reaction in which the spinel crystals crack open and release metal atoms. These metal atoms may act as nuclei for metallization (e.g., reductive copper coating). Additionally, the laser creates a microscopically irregular surface and abrades the polymer matrix to create numerous microscopic depressions and grooves in which copper can adhere during metallization.

[0032]

[0047] If desired, the conductive elements may be antenna elements (e.g., antenna resonating elements) such that the resulting component forms an antenna system. The conductive elements may form a variety of different types of antennas, such as antennas having resonating elements formed from patch antenna elements, inverted-F antenna elements, closed and open slot antenna elements, loop antenna elements, monopoles, dipoles, planar inverted-F antenna elements, hybrids of these designs, and the like. The resulting antenna systems may be utilized in a variety of different electronic components. By way of example, the antenna systems may be formed into electronic components such as desktop computers, lightweight computers, handheld electronic devices, automotive equipment, and the like. In one preferred configuration, the antenna systems are formed into the housings of relatively small lightweight electronic components that have relatively little available interior space. Examples of suitable lightweight electronic components include mobile phones, laptop computers, small lightweight computers (e.g., ultralight computers, netbook computers, and tablet computers), wristwatch devices, pendant devices, headphone and earpiece devices, media players with wireless communication capabilities, handheld computers (sometimes referred to as personal digital assistants), remote controllers, satellite positioning system (GPS) devices, handheld gaming devices, and the like. The antenna may also be integral with other components of the handheld device, such as the camera module, speaker or battery cover.

[0033]

[0048] One particularly suitable electronic component shown in Figures 1-2 is a handheld device 10 with mobile phone capabilities. As shown in Figure 1, the device 10 may have a housing 12 formed from plastic, metal, other suitable dielectric material, other suitable conductive material, or a combination of such materials. A display 14, such as a touch screen display, may be provided on the front side of the device 10. The device 10 may also have a speaker port 40 and other input / output ports. One or more buttons 38 and other user input devices may be used to gather user input. As shown in Figure 2, an antenna system 26 is also provided on a back side 42 of the device 10, although it should be understood that the antenna system may generally be located at any desired location on the device. The antenna system may be electrically connected to other components within the electronic device using any of a variety of known techniques. Referring again to Figures 1-2, for example, the housing 12 or a portion of the housing 12 may serve as a conductive ground plane for the antenna system 26. 3, which shows that antenna system 26 is fed by a radio frequency source 52 at a positive antenna feed terminal 54 and a ground antenna feed terminal 56. Positive antenna feed terminal 54 may be coupled to an antenna resonating element 58, and ground antenna feed terminal 56 may be coupled to a ground element 60. Resonating element 58 may have a main arm 46 and a shorting branch 48 connecting main arm 46 to ground 60.

[0034]

[0049] Various other configurations for electrically connecting the antenna system are also contemplated. For example, in FIG. 4, the antenna system is based on a monopole antenna configuration, with the resonating element 58 having a serpentine shape. In such an embodiment, the feed terminal 54 may be connected to one end of the resonating element 58, and the ground feed terminal 56 may be coupled to the housing 12 or another suitable ground plane element. In another embodiment shown in FIG. 5, the conductive antenna element 62 is configured to define a closed slot 64 and an open slot 66. The antenna formed from the structure 62 may be fed using the positive antenna feed terminal 54 and the ground antenna feed terminal 56. In this type of arrangement, the slots 64 and 66 serve as antenna resonating elements for the antenna element 26. The size of the slots 64 and 66 may be configured for the antenna element 26 to operate in the desired communication band (e.g., 2.4 GHz and 5 GHz, etc.). Another possible configuration for the antenna system 26 is shown in FIG. 6. In this embodiment, antenna element 26 has a patch antenna resonating element 68 and may be fed using positive antenna feed terminal 54 and ground antenna feed terminal 56. Ground 60 may be coupled to housing 12 or other suitable ground plane element of device 10. FIG. 7 illustrates yet another exemplary configuration that may be used for antenna elements of antenna system 26. As shown, antenna resonating element 58 has two main arms 46A and 46B. Arm 46A is shorter than arm 46B and is therefore associated with a higher frequency of operation than arm 46A. By using two or more separate resonating element structures of different sizes, antenna resonating element 58 can be configured to cover a wider bandwidth or more than one desired communications band.

[0035]

[0050] In certain embodiments of the present invention, the polymeric compositions may be particularly well suited for high frequency antennas and antenna arrays used in base stations, repeaters (e.g., "femtocells"), relay stations, terminals, user devices and / or other suitable components of 5G systems. As used herein, "5G" generally refers to high speed data communication by radio frequency signals. 5G networks and systems can communicate data at much higher speeds than previous generation data communication standards (e.g., "4G", "LTE"). For example, "5G frequencies" as used herein may refer to frequencies of 1.5 GHz or higher, in some embodiments about 2.0 GHz or higher, in some embodiments about 2.5 GHz or higher, in some embodiments about 3.0 GHz or higher, in some embodiments about 3 GHz to about 300 GHz or higher, in some embodiments about 4 GHz to about 80 GHz, in some embodiments about 5 GHz to about 80 GHz, in some embodiments about 20 GHz to about 80 GHz, and in some embodiments about 28 GHz to about 60 GHz. Various standards and specifications have been published that quantify the requirements for 5G communications. As an example, the International Telecommunications Union (ITU) published the International Mobile Telecommunications-2020 ("IMT-2020") standard in 2015. The IMT-2020 standard defines various data transmission criteria (e.g., downlink and uplink data rates, latency, etc.) for 5G. The IMT-2020 standard specifies uplink and downlink peak data rates as the minimum data rates for uploading and downloading data that a 5G system must support. The IMT-2020 standard sets the downlink peak data rate requirement at 20 Gbit / s and the uplink peak data rate at 10 Gbit / s. As another example, the 3G-SDI standard specifies the maximum data rate for 5G (5G LTE) and the maximum data rate for 5G (5G LTE). rdThe Third Generation Partnership Project (3GPP) recently published a new standard for 5G, referred to as "5G NR." 3GPP published "Release 15" in 2018, which defines "Phase 1" as the standardization of 5G NR. 3GPP defines the 5G frequency bands as "Frequency Range 1" (FR1), which generally includes frequencies below 6 GHz, and "Frequency Range 2" (FR2), which is the frequency band in the range of 20-60 GHz. The antenna systems described herein may meet or be considered "5G" based on standards published by 3GPP, such as Release 15 (2018), and / or the IMT-2020 standard.

[0036]

[0051] To achieve high-speed data communication at high frequencies, antenna elements and arrays may utilize small feature sizes / spacings (e.g., fine pitch technology) that can improve antenna performance. For example, the feature size (spacing between antenna elements, width of antenna elements), etc., generally depends on the wavelength ("λ") of the desired transmit and / or receive radio frequency propagating through the dielectric of the substrate on which the antenna elements are formed (e.g., nλ / 4, where n is an integer). Additionally, beamforming and / or beamsteering can be utilized to facilitate transmission and reception across multiple frequency ranges or channels (e.g., multiple-input multiple-output (MIMO), massive MIMO).

[0037]

[0052] High frequency 5G antenna elements may have various configurations. For example, 5G antenna elements may be or include coplanar waveguide elements, patch arrays (e.g., mesh grid patch arrays), other suitable 5G antenna configurations. Antenna elements may be configured to provide MIMO, massive MIMO capabilities, beam steering, and the like. As used herein, "massive" MIMO capabilities generally refer to providing a large number of transmit and receive channels by an antenna array, for example, eight transmit (Tx) channels and eight receive (Rx) channels (abbreviated as 8x8). Massive MIMO capabilities may include 8x8, 12x12, 16x16, 32x32, 64x64, or more.

[0038]

[0053] The antenna elements may have various configurations and arrangements and may be fabricated using various manufacturing techniques. As an example, the antenna elements and / or associated elements (e.g., ground elements, feedlines, etc.) may utilize fine pitch technology. Fine pitch technology generally refers to small or fine spacing between their components or leads. For example, the feature size and / or spacing between antenna elements (or between antenna elements and ground planes) may be about 1,500 micrometers or less, in some embodiments 1,250 micrometers or less, in some embodiments 750 micrometers or less (e.g., center-to-center spacing of 1.5 mm or less), 650 micrometers or less, in some embodiments 550 micrometers or less, in some embodiments 450 micrometers or less, in some embodiments 350 micrometers or less, in some embodiments 250 micrometers or less, in some embodiments 150 micrometers or less, in some embodiments 100 micrometers or less, and in some embodiments 50 micrometers or less. However, it should be understood that smaller and / or larger feature sizes and / or spacings may be utilized within the scope of the present disclosure.

[0039]

[0054] As a result of such small feature sizes, antenna systems with a large number of antenna elements within a small footprint can be achieved. For example, the antenna array may have an average antenna element density of more than 1,000 antenna elements per square centimeter, in some embodiments more than 2,000 antenna elements per square centimeter, in some embodiments more than 3,000 antenna elements per square centimeter, in some embodiments more than 4,000 antenna elements per square centimeter, in some embodiments more than 6,000 antenna elements per square centimeter, and in some embodiments more than about 8,000 antenna elements per square centimeter. Such a dense arrangement of antenna elements can provide a larger number of channels for MIMO functionality per unit area of ​​antenna area. For example, the number of channels may correspond to (e.g., be equal to or proportional to) the number of antenna elements.

[0040]

[0055] 8, an embodiment of a 5G antenna system 100 is shown that includes a base station 102, one or more relay stations 104, one or more user computing devices 106, one or more Wi-Fi repeaters 108 (e.g., “femtocells”), and / or other suitable antenna components of the 5G antenna system 100. The relay stations 104 may be configured to relay or “repeat” signals between the base station 102 and the user computing devices 106 and / or the relay stations 104 to facilitate communication with the base station 102 by the user computing devices 106 and / or other relay stations 104. The base station 102 may include a MIMO antenna array 110 configured to receive and / or transmit radio frequency signals 112 with the relay stations 104, the Wi-Fi repeaters 108, and / or directly with the user computing devices 106. The user computing devices 106 is not necessarily limited by the present invention and includes devices such as 5G smartphones.

[0041]

[0056] The MIMO antenna array 110 may utilize beam steering to focus or direct radio frequency signals 112 to the relay station 104. For example, the MIMO antenna array 110 may be configured to adjust an elevation angle 114 with respect to a heading angle 116 defined in the XY and / or ZY planes, as well as with respect to the Z direction. Similarly, one or more of the relay station 104, user computing device 106, and Wi-Fi repeater 108 may utilize beam steering to improve reception and / or transmission capabilities to the MIMO antenna array 110 by directionally tuning the sensitivity and / or power transmission of the devices 104, 106, 108 with respect to the MIMO antenna array 110 of the base station 102 (e.g., by adjusting one or both of the relative elevation angle and / or relative azimuth angle of the respective devices).

[0042]

[0057] 9A and 9B are top and side views, respectively, of an exemplary user computing device 106. The user computing device 106 may include one or more antenna elements 200, 202 (e.g., arranged as an antenna array). With reference to FIG. 9A, the antenna elements 200, 202 may be configured to perform beam steering in the XY plane (indicated by arrows 204, 206, corresponding to relative azimuth angles). With reference to FIG. 9B, the antenna elements 200, 202 may be configured to perform beam steering in the ZY plane (indicated by arrows 204, 206).

[0043]

[0058] 10 is a simplified schematic diagram of multiple antenna arrays 302 connected (e.g., with a front-end module) using respective feed lines 304. The antenna array 302 may be attached to a side 306 of a substrate 308, which may be formed from a polymer composition of the present invention. The antenna array 302 may include a plurality of vertically connected elements (e.g., a mesh grid array). Thus, the antenna array 302 may extend generally parallel to the side 306 of the substrate 308. A shield may optionally be provided on the side 306 of the substrate 308 such that the antenna array 302 is located outside the shield with respect to the substrate 308. The vertical spacing distance between the vertically connected elements of the antenna array 302 may be approximately 1 / 2 the length of the antenna array 302. 302 Accordingly, in some embodiments, these spacing distances may be relatively small (e.g., less than about 750 micrometers) such that the antenna array 302 is a “fine pitch” antenna array 302.

[0044]

[0059] 11 is a side view of a configuration of a coplanar waveguide antenna 400. One or more coplanar ground layers 402 may be disposed parallel to an antenna element 404 (e.g., a patch antenna element). Another ground layer 406 may be spaced apart from the antenna element 404 by a substrate 408, which may be formed from the polymer composition of the present invention. One or more additional antenna elements 410 may be spaced apart from the antenna element 404 by a second layer or substrate 412, which may also be formed from the polymer composition of the present invention. The dimensions "G" and "W" may correspond to the "feature size" of the antenna 400. The "G" dimension may correspond to the distance between the antenna element 404 and the coplanar ground layer 406. The "W" dimension may correspond to the width (e.g., line width) of the antenna element 404. Thus, in some embodiments, the dimensions "G" and "W" may be relatively small (e.g., less than about 750 micrometers) such that the antenna 400 is a "fine pitch" antenna 400.

[0045]

[0060] FIG. 12A is a diagram of an antenna array 500 according to another aspect of the disclosure. The antenna array 500 may include a substrate 510 formable from the polymer composition of the present invention and a plurality of antenna elements 520 formed thereon. The plurality of antenna elements 520 may be approximately uniformly sized in the X and / or Y directions (e.g., square or rectangular). The plurality of antenna elements 520 may be approximately uniformly spaced apart in the X and Y directions. The dimensions of and / or spacing between the antenna elements 520 may correspond to the "feature size" of the antenna array 500. Thus, in some embodiments, the dimensions and / or spacing may be relatively small (e.g., less than about 750 micrometers) such that the antenna array 500 is a "fine pitch" antenna array 500. As illustrated by ellipsis 522, the number of columns of antenna elements 520 illustrated in FIG. 12 is shown by way of example only. Similarly, the number of rows of antenna elements 520 is shown by way of example only.

[0046]

[0061] The tuned antenna array 500 can be used to provide massive MIMO capabilities, for example, in a base station (e.g., as described above with respect to FIG. 8). More specifically, radio frequency interactions between various elements may be controlled or tuned to provide multiple transmit and / or receive channels. The transmit power and / or receive sensitivity may be directionally controlled to focus or direct the radio frequency signal, for example, as described with respect to the radio frequency signal 112 of FIG. 8. The tuned antenna array 500 can provide a large number of antenna elements 522 within a small footprint. For example, the tuned antenna 500 may have an average antenna element density of 1,000 or more antenna elements per square centimeter. Such a dense arrangement of antenna elements can provide a larger number of channels for MIMO capabilities per unit area. For example, the number of channels may correspond to (e.g., be equal to or proportional to) the number of antenna elements.

[0047]

[0062] FIG. 12B is a diagram of an antenna array 540 formed by laser direct structuring that can be optionally utilized to form antenna elements. The antenna array 540 may include a plurality of antenna elements 542 and a plurality of feedlines 544 connecting the antenna elements 542 (e.g., with other antenna elements 542, front-end modules, or other suitable components). The antenna elements 542 may have respective widths "w" and spacing distances "S1" and "S2" therebetween (e.g., in the X- and Y-directions, respectively). These dimensions may be selected to achieve 5G frequency communication at a desired 5G frequency. More specifically, the dimensions may be selected to tune the antenna array 540 to transmit and / or receive data using radio frequency signals within the 5G frequency spectrum. The dimensions may be selected based on material properties of the substrate. For example, one or more of "w", "S1", or "S2" may correspond to a plurality of propagation wavelengths ("λ") of a desired frequency through the substrate material (e.g., nλ / 4, where n is an integer).

[0048]

[0063] As an example, λ can be:

[0049]

number

[0050] (where c is the speed of light in a vacuum and ε R is the relative dielectric constant of the substrate (or surrounding material) and f is the desired frequency) It may be calculated as follows:

[0051]

[0064] 12C is a diagram of an exemplary antenna configuration 560 according to an embodiment of the present disclosure. The antenna configuration 560 may include multiple antenna elements 562 disposed on parallel long sides of a substrate 564 formable from the polymer composition of the present invention. The various antenna elements 562 may have respective lengths "L" (and spacing distances therebetween) that tune the antenna configuration 560 to receive and / or transmit at a desired frequency and / or frequency range. More particularly, such dimensions may be selected based on the propagation wavelength λ at a desired frequency for the substrate material, e.g., as described above with reference to FIG. 12B.

[0052]

[0065] 13A-13C are simplified sequence diagrams of a laser direct structuring manufacturing method that can be used to form antenna elements and / or arrays according to aspects of the present disclosure. With reference to FIG. 13A, a substrate 600 may be formed from the polymer composition of the present invention using any desired technique (e.g., injection molding). In certain embodiments, as shown in FIG. 13B, a laser 602 may be used to activate a laser activatable additive to form a circuit pattern 604 that may include one or more of the antenna elements and / or arrays. For example, the laser may melt conductive particles in the polymer composition to form the circuit pattern 604. With reference to FIG. 13C, the substrate 600 may be immersed in an electroless copper bath to plate the circuit pattern 604 to form antenna elements, element arrays, other components and / or conductive lines therebetween.

[0053]

[0066] The invention may be better understood with reference to the following examples. Test Method

[0067] Melt viscosity: Melt viscosity (Pa s) was measured at a shear rate of 400 s using a Dynisco LCR7001 capillary rheometer. -1and 15°C above the melt temperature (e.g., about 350°C) according to ISO Test No. 11443:2005. The rheometer orifice (die) had a diameter of 1 mm, a length of 20 mm, an L / D ratio of 20.1, and an entrance angle of 180°. The barrel diameter was 9.55 mm + 0.005 mm and the rod length was 233.4 mm.

[0054]

[0068] Melting temperature: Melting temperature ("Tm") may be determined by differential scanning calorimetry ("DSC") as known in the art. Melting temperature is the differential scanning calorimetry (DSC) peak melting temperature as determined by ISO test No. 11357-2:2013. Based on the DSC procedure, samples were heated and cooled at 20°C per minute using DSC measurements performed on a TA Q2000 instrument as described in ISO standard 10350.

[0055]

[0069] Deflection Temperature Under Load ("DTUL"): Deflection temperature under load may be determined according to ISO Test No. 75-2:2013 (technically equivalent to ASTM D648-07). More specifically, a test specimen sample of 80 mm length, 10 mm thickness, and 4 mm width may be subjected to an edgewise three-point bend test with a specified load (maximum external fiber stress) of 1.8 megapascals. The specimen is lowered into a silicone oil bath and the temperature is increased at 2°C per minute until the specimen deflects 0.25 mm (0.32 mm per ISO Test No. 75-2:2013).

[0056]

[0070] Tensile modulus, tensile stress and tensile elongation: Tensile properties may be tested according to ISO Test No. 527:2012 (technically equivalent to ASTM D638-14). Modulus and strength measurements may be performed on the same test specimen sample of 80 mm length, 10 mm thickness, and 4 mm width. The test temperature may be 23°C and the test speed may be 1 or 5 mm / min.

[0057]

[0071] Flexural modulus, flexural stress and flexural elongation: Flexural properties may be tested according to ISO Test No. 178:2010 (technically equivalent to ASTM D790-10). The test may be performed on a support span of 64 mm. The test may be performed at the center of an uncut ISO 3167 multipurpose bar. The test temperature may be 23°C and the test speed may be 2 mm / min.

[0058]

[0072] Unnotched and Notched Charpy Impact Strength: Charpy properties may be tested according to ISO Test No. ISO179-1:2010 (technically equivalent to ASTM D256-10, Method B). This test may be performed using a Type 1 specimen size (80 mm length, 10 mm width, and 4 mm thickness). When testing notched impact strength, the notch may be a Type A notch (0.25 mm base radius). Specimens may be cut from the center of the multipurpose bar using a single-tooth milling machine. The test temperature may be 23°C.

[0059]

[0073] Dielectric constant ("Dk") and dissipation factor ("Df"): The dielectric constant (or relative static permittivity) and dissipation factor are determined by Baker-Jarvis et al., IEEE Trans. on Dielectric and Electrical Insulation, 5(4), 571 (1998) and Krupka et al., Proc. th It is determined using a known split-post dielectric resonance method such as that described in International Conference on Dielectric Materials: Measurements and Applications, IEEE Conference Publication No. 430 (September 1996). More specifically, a plate-shaped sample of size 80 mm x 80 mm x 1 mm was inserted between two fixed dielectric resonators. The resonators measured the dielectric constant components at the plane of the specimen. Five samples were tested and the average value was recorded. Using the split-post resonator, dielectric measurements can be made in the low gigahertz range, e.g., 1 GHz to 2 GHz.

[0060]

[0074] Thermal cycling test: The specimen is placed in a temperature controlled chamber and heated / cooled within a temperature range of -30°C to 100°C. The specimen is first heated until it reaches a temperature of 100°C, at which point it is immediately cooled. When the temperature reaches -30°C, the specimen is immediately heated again until it reaches 100°C. 23 heating / cooling cycles may be performed over a 3 hour period.

[0061] Example 1

[0075] Samples 1-5 are formed from various combinations of liquid crystal polymers (LCP1, LCP2, LCP3 or LCP4), titanium dioxide, graphite, copper chromite filler (CuCr2O4), glass fiber and alumina trihydrate. LCP1 is formed from 48% HNA, 2% HBA, 25% BP and 25% TA. LCP2 is formed from 43% HBA, 20% NDA, 9% TA and 28% HQ. LCP3 is formed from 73% HBA and 27% HNA. LCP4 is formed from 60% HBA, 4.2% HNA, 17.9% TA and 17.9% BP. Compounding was performed using an 18 mm single screw extruder. Parts are injection molded and samples are cut into plates (60 mm x 60 mm).

[0062] [Table 1]

[0063]

[0076] Samples 1-5 were tested for thermal and mechanical properties and the results are listed in Table 2 below.

[0064] [Table 2]

[0065] Example 2

[0077] Samples 6-10 are formed from various combinations of liquid crystal polymers (LCP1, LCP2 or LCP3), titanium dioxide, graphite or carbon fiber, glass fiber, alumina trihydrate and PPS. Compounding was carried out using an 18 mm single screw extruder. Parts were injection molded and samples were molded into plaques (60 mm x 60 mm).

[0066] [Table 3]

[0067]

[0078] Samples 6-10 were tested for thermal and mechanical properties and the results are listed in Table 4 below.

[0068] [Table 4]

[0069] Example 3

[0079] Samples 11-15 are formed from various combinations of liquid crystal polymers (LCP2, LCP3 or LCP4), titanium dioxide, graphite, copper chromite filler (CuCr2O4), glass fiber and alumina trihydrate. Compounding was performed using an 18 mm single screw extruder. Parts were injection molded and samples were molded into plaques (80 mm x 80 mm x 3 mm).

[0070] [Table 5]

[0071]

[0080] Samples 11-15 were tested for thermal and mechanical properties and the results are listed in Table 6 below.

[0072] [Table 6]

[0073] Example 4

[0081] Samples 16-22 are formed from various combinations of liquid crystal polymers (LCP2, LCP3, or LCP4), graphite, carbon fiber, copper chromite filler (CuCr2O4), and glass fiber. Compounding was performed using an 18 mm single screw extruder. Parts were injection molded and samples were molded into plaques (60 mm x 60 mm).

[0074] [Table 7]

[0075]

[0082] Samples 16-22 were tested for thermal and mechanical properties and the results are listed in Table 8 below.

[0076] [Table 8]

[0077] Example 5

[0083] Samples 23 to 27 were prepared using a variety of materials, including liquid crystal polymers (LCP2, LCP3, or LCP4), copper chromite (CuCr2O4), glass fibers, zinc oxide single crystals, tetrapod whiskers (Pana-Tetra™ manufactured by Panasonic), conductive graphite and / or semiconductive graphite (Krefine™ manufactured by Kureha Extron, with a volume resistivity of 3×10 7 The materials were formulated from various combinations of modulus (ohm·cm). Compounding was carried out using an 18 mm single screw extruder. Parts were injection molded and samples were cut into plaques (60 mm × 60 mm).

[0078] [Table 9]

[0079]

[0084] Samples 23-27 were tested for electrical, thermal and mechanical properties and the results are listed in Table 10 below.

[0080] [Table 10]

[0081]

[0085] Sample 27 was also subjected to the thermal cycling test described above. After the test, the dielectric constant was determined to be 11.36 and the dielectric loss tangent was determined to be 0.1566. Thus, the ratio of the dielectric constant after the thermal cycling test to the initial dielectric constant was 0.96, and the ratio of the dielectric loss tangent after the thermal cycling test to the initial dielectric loss tangent was 0.75.

[0082] Example 6

[0086] Samples 28-30 are formed from various combinations of liquid crystal polymers (LCP2, LCP3, or LCP4), carbon fiber, copper chromite filler (CuCr2O4), and glass fiber. Compounding was performed using a 32 mm twin screw extruder. Parts were injection molded and samples were molded into plaques (80 mm x 90 mm x 3 mm).

[0083] [Table 11]

[0084]

[0087] Samples 28-30 were tested for thermal and mechanical properties and the results are listed in Table 12 below.

[0085] [Table 12]

[0086]

[0088] Samples 28 to 30 were also subjected to the thermal cycling test described above. After the test, the dielectric loss tangents obtained for the samples were determined to be 0.032, 0.025, and 0.020, respectively. Thus, the ratios of the dielectric loss tangent after the thermal cycling test to the initial dielectric loss tangent for samples 28, 29, and 30 were 1.14, 1.26, and 1.13, respectively.

[0087] Example 7

[0089] Samples 31-34 are formed from various combinations of liquid crystal polymers (LCP2, LCP3, or LCP4), alumina trihydrate (ATH), titanium dioxide, carbon fiber, copper chromite filler (CuCr2O4), and glass fiber. Compounding was performed using a 32 mm twin screw extruder. Parts were injection molded and samples were molded into plaques (80 mm x 90 mm x 3 mm).

[0088] [Table 13]

[0089]

[0090] Samples 31-34 were tested for thermal and mechanical properties and the results are listed in Table 14 below.

[0090] [Table 14]

[0091] Example 8 Samples 35-40 are made from various combinations of liquid crystal polymers (LCP2, LCP3, or LCP4), alumina trihydrate (ATH), titanium dioxide, carbon fiber, copper chromite filler (CuCr2O4), and glass fiber. Compounding was performed using a 32 mm twin screw extruder. Parts were injection molded and samples were molded into plaques (80 mm x 90 mm x 3 mm).

[0092] [Table 15]

[0093]

[0092] Samples 35-40 were tested for thermal and mechanical properties, and the results are listed in Table 16 below.

[0094] [Table 16]

[0095]

[0093] Samples 38 to 40 were also subjected to the thermal cycle test described above. After the test, the dielectric loss tangents obtained for the samples were determined to be 0.01764, 0.0155, and 0.0142, respectively. Thus, the ratios of the dielectric loss tangents after the thermal cycle test to the initial dielectric loss tangents for Samples 38, 39, and 40 were 0.84, 0.91, and 0.89, respectively.

[0096] Example 9 Samples 41-43 are made from various combinations of liquid crystal polymers (LCP2, LCP3, or LCP4), alumina trihydrate (ATH), titanium dioxide, carbon fiber, copper chromite filler (CuCr2O4), and glass fiber. Compounding was performed using a 32 mm twin screw extruder. Parts were injection molded and samples were molded into plaques (80 mm x 90 mm x 3 mm).

[0097] [Table 17]

[0098]

[0095] Samples 41-43 were tested for thermal and mechanical properties, and the results are set forth in Table 18 below.

[0099] [Table 18]

[0100]

[0096] Samples 41 to 43 were also subjected to the above-mentioned thermal cycle test. After the test, the dielectric constants obtained for the samples were determined to be 14.1, 13.2 and 16.6, respectively. Thus, the ratios of the dielectric constants after the thermal cycle test to the initial dielectric constants of samples 41, 42 and 43 were 0.99, 0.99 and 0.98, respectively. Also, the dielectric loss tangents obtained for the samples were determined to be 0.020, 0.020 and 0.021, respectively. Thus, the ratios of the dielectric loss tangent after the thermal cycle test to the initial dielectric loss tangent of samples 41, 42 and 43 were 1.18, 1.18 and 1.10, respectively.

[0101] Example 10 Samples 44-47 are made from various percentages of liquid crystal polymers ("LCP5" and "LCP3"), wollastonite fiber (Nyglos™ 8), black pigment, carbon fiber and lubricant (Glycolube™ P). LCP5 is made from 60 mol.% HBA, 5 mol.% HNA, 12% mol.% BP, 17.5 mol.% TA and 5 mol.% APAP. Compounding was carried out using an 18 mm single screw extruder. Parts are injection molded and samples are cut into plaques (60 mm x 60 mm).

[0102] [Table 19]

[0103]

[0098] Samples 44-47 were tested for thermal and mechanical properties, and the results are set forth in Table 20 below.

[0104] [Table 20]

[0105]

[0099] Samples 46-47 were also subjected to the thermal cycle test described above. After the test, the dielectric constants obtained for the samples were determined to be 12.9 and 12.6, respectively. Thus, the ratios of the dielectric constants after the thermal cycle test to the initial dielectric constants of samples 46 and 47 were 0.99 and 1.0, respectively. Also, the dielectric loss tangents obtained for the samples were determined to be 0.021 and 0.015, respectively. Thus, the ratios of the dielectric loss tangents after the thermal cycle test to the initial dielectric loss tangent of samples 46 and 47 were 1.2 and 0.83, respectively.

[0106] Example 11 Samples 48-51 are formulated with various percentages of Liquid Crystal Polymers ("LCP5" and "LCP3"), Nyglos™ 8, black pigment, graphite, and Glycolube™ P. Compounding was carried out using an 18 mm single screw extruder. Parts were injection molded and samples were molded into plaques (60 mm x 60 mm).

[0107] [Table 21]

[0108]

[0101] Samples 48-51 were tested for thermal and mechanical properties, and the results are listed in Table 22 below.

[0109] [Table 22]

[0110]

[0102] Samples 48-50 were also subjected to the thermal cycle test described above. After the test, the dielectric constants obtained for the samples were determined to be 12.6, 8.9 and 6.29, respectively. Thus, the ratios of the dielectric constants after the thermal cycle test to the initial dielectric constants of samples 48, 49 and 50 were 1.0, 1.0 and 1.0, respectively. Also, the dielectric loss tangents obtained for the samples were determined to be 0.0578, 0.0214 and 0.0098, respectively. Thus, the ratios of the dielectric loss tangent after the thermal cycle test to the initial dielectric loss tangent of samples 48, 49 and 50 were 1.17, 1.06 and 1.09, respectively.

[0111] Example 12

[0103] Samples 52-56 are made from various combinations of liquid crystal polymers (LCP2 or LCP3), alumina trihydrate (ATH), titanium dioxide, carbon fiber, and glass fiber. Compounding was carried out using a 32 mm twin screw extruder. Parts were injection molded and samples were molded into plaques (80 mm x 90 mm x 3 mm).

[0112] [Table 23]

[0113]

[0104] Samples 52-56 were tested for thermal and mechanical properties, and the results are set forth in Table 24 below.

[0114] [Table 24]

[0115] Example 12

[0105] Samples 57-58 are made from various combinations of liquid crystal polymers (LCP2, LCP3 or LCP4), alumina trihydrate (ATH), titanium dioxide, carbon fiber, copper chromite filler (CuCr2O4), and glass fiber. Compounding was carried out using a 32 mm twin screw extruder. Parts were injection molded and samples were molded into plaques (80 mm x 90 mm x 3 mm).

[0116] [Table 25]

[0117]

[0106] Sample 58 was tested for thermal and mechanical properties and the results are set forth in Table 26 below.

[0118] [Table 26]

[0119]

[0107] These and other modifications and variations of the present invention are intended to be within the spirit and scope of the present invention. It will be understood that the present invention can be practiced by those skilled in the art without departing from the spirit and scope of the present invention. Moreover, it should be understood that aspects of the various embodiments may be interchanged both in whole or in part. Moreover, those skilled in the art will appreciate that the foregoing description is merely illustrative, and thus does not limit the invention as further described in the appended claims. The claims as filed are set forth below. [Claim 1] 1. A polymer composition comprising a dielectric material distributed within a polymer matrix, the dielectric material having a thickness of from about 0.1 ohm·cm to about 1×10 12 A polymeric composition having a volume resistivity of ohms·cm, the polymeric matrix containing at least one thermotropic liquid crystal polymer, and further wherein the polymeric composition exhibits a dielectric constant of greater than or equal to about 4 and a dielectric loss tangent of less than or equal to about 0.3, as determined at a frequency of 2 GHz. [Claim 2] 2. The polymer composition of claim 1, exhibiting a dielectric constant after exposure to a temperature cycle of about -30°C to about 100°C, wherein the ratio of the dielectric constant after the temperature cycle to the dielectric constant before the thermal cycle is about 0.8 or greater. [Claim 3] 3. The polymer composition of claim 1, wherein the polymer composition exhibits a dielectric tangent after exposure to a temperature cycle of about -30°C to about 100°C, and the ratio of the dielectric tangent after the temperature cycle to the dielectric tangent before the thermal cycle is about 1.3 or less. [Claim 4] 4. The polymer composition according to claim 1, wherein the polymer composition exhibits a dielectric loss tangent after exposure to a temperature cycle of about -30°C to about 100°C, and the ratio of the dielectric loss tangent after the temperature cycle to the dielectric loss tangent before the thermal cycle is about 1.0 or less. [Claim 5] 5. The polymer composition according to claim 1, wherein the dielectric material comprises an inorganic oxide material. [Claim 6] 6. The polymer composition of claim 5, wherein the inorganic oxide material comprises titanium dioxide particles. [Claim 7] 6. The polymer composition of claim 5, wherein the inorganic oxide material comprises inorganic oxide whiskers. [Claim 8] 8. The polymer composition of claim 7, wherein the whiskers are zinc oxide whiskers. [Claim 9] 8. The polymer composition of claim 7, wherein the whiskers have a central body and a plurality of needle-like crystals extending radially therefrom. [Claim 10] 10. The polymer composition of claim 1, wherein the dielectric material comprises an inorganic oxide material having a volume resistivity of from 0.1 ohm·cm to about 500 ohm·cm. [Claim 11] The dielectric material is approximately 1×10 3 ~Approx. 1×10 12 11. The polymer composition of claim 1, comprising a carbon material having a volume resistivity of ohm·cm. [Claim 12] The dielectric material is a conductive material having a volume resistivity of less than about 0.1 ohm cm and a dielectric constant of less than about 1×10 12 12. The polymer composition according to claim 1, comprising an insulating material having a volume resistivity greater than ohm·cm. [Claim 13] 13. The polymer composition of claim 12, wherein the conductive material comprises a carbon material and the insulating material comprises an inorganic oxide material. [Claim 14] 14. The polymer composition of claim 13, wherein the ratio of the weight percentage of the inorganic oxide material to the weight percentage of the carbon material is from about 3 to about 100. [Claim 15] 15. The polymer composition according to claim 1, wherein the thermotropic liquid crystal polymer is an aromatic polyester containing repeating units derived from 4-hydroxybenzoic acid. thing. [Claim 16] 16. The polymer composition of claim 1, wherein the thermotropic liquid crystal polymer has a total amount of repeat units derived from naphthenic hydroxycarboxylic acids and / or naphthenic dicarboxylic acids of about 10 mol.% or more. [Claim 17] 17. The polymer composition of claim 16, wherein the thermotropic liquid crystal polymer has a total amount of repeat units derived from naphthalene-2,6-dicarboxylic acid of about 10 mol.% or more. [Claim 18] 18. The polymer composition of claim 1, further comprising a laser activatable additive. [Claim 19] The laser activatable additive has the following general formula: AB2O4 (In the formula, A is a metal cation having a valence of 2; B is a metal cation having a valence of 3. 20. The polymer composition of claim 18, comprising spinel crystals having the formula: [Claim 20] 20. The polymer composition of claim 19, wherein the spinel crystals comprise MgAl2O4, ZnAl2O4, FeAl2O4, CuFe2O4, CuCr2O4, MnFe2O4, NiFe2O4, TiFe2O4, FeCr2O4, MgCr2O4, or combinations thereof. [Claim 21] 21. The polymer composition according to any one of claims 1 to 20, further comprising a fibrous filler. [Claim 22] 22. The polymer composition of claim 21, wherein the fibrous filler comprises glass fibers. [Claim 23] 1,000 seconds -1 23. The polymer composition according to claim 1, having a melt viscosity of about 5 to about 100 Pa·s, determined at a shear rate of 100° C. and a temperature of 350° C. [Claim 24] 24. The polymer composition of any one of claims 1 to 23, comprising about 15 wt.% to about 85 wt.% of a thermotropic liquid crystal polymer and about 10 wt.% to about 70 wt.% of a dielectric material. [Claim 25] 25. A moulded part comprising the polymer composition according to any one of claims 1 to 24. [Claim 26] 26. The molded part of claim 25, wherein one or more conductive elements are formed on a surface of the part. [Claim 27] 25. An antenna system comprising a polymer composition according to any one of claims 1 to 24 and a substrate comprising at least one antenna element configured to transmit and receive radio frequency signals, the antenna element being coupled to the substrate. [Claim 28] 28. The antenna system of claim 27, wherein the radio frequency signal is a 5G signal. [Claim 29] 30. The antenna system of claim 27, wherein at least one antenna element has a feature size of less than about 1,500 micrometers. [Claim 30] 28. The antenna of claim 27, wherein the at least one antenna element comprises a plurality of antenna elements. Tena System. [Claim 31] 31. The antenna system of claim 30, wherein the plurality of antenna elements are separated by a spacing distance of less than about 1,500 micrometers. [Claim 32] 31. The antenna system of claim 30, wherein the plurality of antenna elements comprises at least 16 antenna elements. [Claim 33] 31. The antenna system of claim 30, wherein the plurality of antenna elements are arranged in an array. [Claim 34] 34. The antenna system of claim 33, wherein the array is configured for at least eight transmit channels and at least eight receive channels. [Claim 35] 34. The antenna system of claim 33, wherein the array has an average antenna element density of greater than 1,000 antenna elements per square centimeter. [Claim 36] 30. The antenna system of claim 27, further comprising a base station, the base station comprising at least one antenna element. [Claim 37] 30. The antenna system of claim 27, further comprising at least one of a user computing device or a repeater, wherein at least one of the user computing device or the repeater base station comprises at least one antenna element.

Claims

1. 1. A polymer composition comprising a dielectric material distributed within a polymer matrix, the dielectric material having a dielectric constant between 0.1 ohm-cm and 1×10 12 the polymer matrix comprises at least one thermotropic liquid crystal polymer, and the polymer composition exhibits a dielectric constant of 4 or greater and a dissipation factor of 0.3 or less, determined at a frequency of 2 GHz; The dielectric material comprises: (a) an inorganic oxide material having a volume resistivity of 0.1 ohm-cm to 500 ohm-cm; (b) a carbon material having a volume resistivity of 1×10 3 ohm-cm to 1×10 12 ohm-cm; (c) carbon fiber and an insulating material having a volume resistivity greater than 1×10 12 ohm-cm; or (d) a conductive material having a volume resistivity of less than 0.1 ohm-cm and an insulating material having a volume resistivity of greater than 1×10 12 ohm-cm, wherein said insulating material comprises 30-60 wt. % of said polymer composition; Including, The polymer composition.

2. The polymer composition of claim 1, exhibiting a dielectric constant after exposure to a temperature cycle from -30°C to 100°C, wherein the ratio of the dielectric constant after the temperature cycle to the dielectric constant before the thermal cycle is 0.8 or greater.

3. The polymer composition of claim 1 or 2, exhibiting a dielectric tangent after exposure to a temperature cycle from -30°C to 100°C, wherein the ratio of the dielectric tangent after the temperature cycle to the dielectric tangent before the thermal cycle is 1.3 or less.

4. A polymer composition described in any of claims 1 to 3, exhibiting a dielectric tangent after exposure to a temperature cycle from -30°C to 100°C, wherein the ratio of the dielectric tangent after the temperature cycle to the dielectric tangent before the thermal cycle is 1.0 or less.

5. The polymer composition of claim 1, wherein the dielectric material comprises an inorganic oxide material.

6. The polymer composition of claim 5, wherein the inorganic oxide material comprises titanium dioxide particles.

7. The polymer composition of claim 5, wherein the inorganic oxide material comprises inorganic oxide whiskers.

8. The polymer composition of claim 7, wherein the whiskers are zinc oxide whiskers.

9. 8. The polymer composition of claim 7, wherein the whiskers have a central body and a plurality of needle-like crystals radiating therefrom.

10. The polymer composition of claim 1, wherein the dielectric material comprises an inorganic oxide material having a volume resistivity of 0.1 ohm-cm to 500 ohm-cm.

11. The dielectric material has a molecular weight of 1×10 3 ~1×10 12 11. The polymer composition of claim 1, comprising said carbon material having a volume resistivity of ohm-cm.

12. The dielectric material comprising the conductive material having a volume resistivity of less than 0.1 ohm-cm and a dielectric constant of less than 1×10 12 said insulating material having a volume resistivity greater than ohm-cm; The polymer composition of any of claims 1 to 11, wherein the insulating material comprises 30 to 60 wt. % of the polymer composition.

13. The polymer composition of claim 12, wherein the conductive material comprises a carbon material and the insulating material comprises an inorganic oxide material.

14. The polymer composition of claim 13, wherein the ratio of the weight percentage of said inorganic oxide material to the weight percentage of said carbon material is 3 to 100.

15. The polymer composition of claim 1, wherein the thermotropic liquid crystal polymer is an aromatic polyester containing repeating units derived from 4-hydroxybenzoic acid.

16. The polymer composition according to claim 1, wherein the thermotropic liquid crystal polymer has a total amount of repeating units derived from naphthenic hydroxycarboxylic acid and / or naphthenic dicarboxylic acid of 10 mol. % or more.

17. The polymer composition according to claim 16, wherein the thermotropic liquid crystal polymer has a total amount of repeating units derived from naphthalene-2,6-dicarboxylic acid of 10 mol. % or more.

18. 18. The polymer composition of any of claims 1 to 17, further comprising a laser activatable additive.

19. The laser activatable additive of claim 1, wherein the laser activatable additive has the following general formula: AB 2 O 4 (In the formula, A is a metal cation having a valence of 2; B is a metal cation having a valence of 3.

20. The polymer composition of claim 18, comprising spinel crystals having the formula:

20. The spinel crystal is MgAl 2 O 4 , ZnAl 2 O 4 , FeAl 2 O 4 , CuFe 2 O 4 , CuCr 2 O 4 , MnFe 2 O 4 , NiFe 2 O 4 , TiFe 2 O 4 , FeCr 2 O 4 , MgCr 2 O 4 20. The polymer composition of claim 19 comprising:

21. 21. The polymer composition of any of claims 1 to 20, further comprising a fibrous filler.

22. The polymer composition of claim 21, wherein the fibrous filler comprises glass fiber.

23. 1,000 seconds -1 23. The polymer composition according to any of claims 1 to 22, having a melt viscosity of 5 to 100 Pa.s determined at a shear rate of 0.5 to 1.0 Pa.s and a temperature of 350°C.

24. The polymer composition according to any one of claims 1 to 23, comprising 15 wt. % to 85 wt. % of a thermotropic liquid crystal polymer and 10 wt. % to 70 wt. % of said dielectric material.

25. A molded part comprising the polymer composition of any of claims 1 to 24.

26. 26. The molded part of claim 25, wherein one or more conductive elements are formed on a surface of the part.

27. 25. An antenna system comprising a polymer composition according to any one of claims 1 to 24 and a substrate comprising at least one antenna element configured to transmit and receive radio frequency signals, said antenna element being coupled to the substrate.

28. The antenna system of claim 27, wherein the radio frequency signal is a 5G signal.

29. The antenna system of claim 27, wherein at least one antenna element has a characteristic size of less than 1,500 micrometers.

30. The antenna system of claim 27, wherein the at least one antenna element includes a plurality of antenna elements.

31. The antenna system of claim 30, wherein the multiple antenna elements are separated by a spacing distance of less than 1,500 micrometers.

32. The antenna system of claim 30, wherein the plurality of antenna elements includes at least 16 antenna elements.

33. The antenna system of claim 30, wherein the plurality of antenna elements are arranged in an array.

34. 34. The antenna system of claim 33, wherein the array is configured for at least eight transmit channels and at least eight receive channels.

35. 34. The antenna system of claim 33, wherein said array has an average antenna element density of greater than 1,000 antenna elements per square centimeter.

36. 30. The antenna system of claim 27, further comprising a base station, said base station comprising said at least one antenna element.

37. 28. The antenna system of claim 27, further comprising at least one of a user computing device or a repeater, said at least one of said user computing device or said repeater base station comprising said at least one antenna element.

Citation Information

Patent Citations

  • Thermoplastic resin composition for high frequency and molded article

    JP2004059702A

  • Tablet for antenna component, antenna component and method for producing the same

    JP2004161953A

  • Highly dielectric resin composition and method for producing the same

    JP2007070446A

  • Liquid crystalline polyester resin composition and molded article thereof

    JP2009155623A

  • Liquid-crystalline polyester blend composition

    JP2011021178A